Analisis Minimalisasi Biaya Obat Antihipertensi antara Kombinasi Ramipril-Spironolakton dengan Valsartan pada Pasien Gagal Jantung Kongestif di Rumah Sakit Pemerintah XY di Jakarta Tahun 2014 - Rahmawati, Cyntiya; Nurwahyuni, Atik (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Hypertension is one of risk factors for congestive heart failure as the top 10 most prevalent diseases in XY Public Hospital in 2014. It has a large number of total cost and cost deviation between hospital and JKN rate. This study aimed to choose an alternative that is more cost-effective to treat congestive heart failure at XY Hospital in 2014. This was a quantitative research using retrospective cross-sectional analysis. The study compared the average value of total cost of two alternative treatments, ramipril-spironolactone with valsartan by using Hospital’s perspective. Direct medical cost components were cost of drugs, cost of physicians’ services and cost of hospitalizations. This study found that: (1) The average total cost of ramipril-spironolactone was Rp.2.527.743; whereas the average total cost of valsartan was Rp.2.430.923; (2) Ramipril-spironolactone’s effectiveness was not significantly different from valsartan; (3) There was cost saving on the average of total cost using valsartan’s drug as many as Rp96.820 per patient; (4) There was cost saving on hospitalization cost using valsartan’s drug for Rp299.031 per patient. Valsartan provided the lowest value and more cost-effective than ramipril-spironolactone for patient with congestive heart failure.